Factors affecting retirement confidence among women in Peninsular Malaysia government sectors - Teo, Tze Juen; Sabri, Mohamad Fazli (Malaysian Consumer and Family Economics Association, 2016)
A majority of employees, particularly women, are hoping for a retirement life that is relaxing and stress-free. In reality, it is almost impossible for these employees to achieve this dream lifestyle. It is this reason that this study is done where it is aimed to uncover factors affecting retirement confidence among women employees in Peninsular Malaysia government sectors. A total of 447 women employees in Peninsular Malaysia government sectors participated in this study. Research data collected from this study revealed that marital status, education level, money adequacy, saving motives, financial literacy, and financial management practices are significant predictors for retirement confidence among women government servants. In essence, women employees in government sectors who are married, achieve tertiary education, have adequate money and are able to save-up for retirement. They are financially literate, able to apply healthy financial management practices and tend to have greater confidence ensuring a secured retirement life.